PERAN VARIABEL PERILAKU BELAJAR INOVATIF, INTENSITAS KERJASAMA KELOMPOK, KEBERSAMAAN VISI DAN RASA SALING PERCAYA DALAM MEMBENTUK KUALITAS SINERGI - Siti Sulasmi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
This paper is an elaborated work on Sulasmi's research (2003) in the oil refinery company, North Sumatera and Liquidified Natural Gas in East Kalimantan, consisting of 100 workgroup in which there are 50 sub-work group.. The research identified the behavior of effective workgroup developing synergetic quality.The result is identified that innovative learning behavior and workgroup intensity contribute to synergetic quality development. The innovative learning behavior dominated the power generating synergetic quality, nevertheless the workgroup intensity is also significantly determined. Furthermore, elaboration is found that the variables of innovative learning behavior and workgroup intensity significantly affected synergetic quality; but if they are accompanied by mutual trust which has the greatest influence, it sets the influential power of innovative learning behavior and workgroup intensity aside. It was found that mutual trust is the primary drive of synergetic quality.